Discovery of missing link between demosponges and hexactinellids confirms palaeontological model of sponge evolution - Joseph P. Botting (Nature Portfolio, 2017)
Abstract The two major extant groups of siliceous sponges, Demospongiae and Hexactinellida, are generally regarded as sister groups forming the clade Silicea, although the nature of their last common ancestor is uncertain. The fossil record contains a diverse range of basal demosponges that appear to have evolved from hexactine-bearing reticulosan ancestors, although a compelling morphological intermediate has not previously been discovered. Here we describe a new species of fossil sponge, Conciliospongia anjiensis gen. et sp. nov., from the Late Ordovician (~444 Ma) Anji Biota of South China. This species has a reticulate, tufted skeleton of minute monaxon spicules, characteristic of the fossil demosponge family Hazeliidae and modern heteroscleromorphs, with hexactine spicules and a globose body form inherited from reticulosan ancestors. This transitional morphology had previously been hypothesized in palaeontological studies. This morphological intermediate between two extant classes further confirms siliceous sponge monophyly and demosponge–hexactinellid spicule homology, and supports the primitive, stem-silicean interpretation of simpler-structured fossil reticulosans.